Analisis Kontingensi untuk Perhitungan Aliran Daya pada Sistem Interkoneksi Tenaga Listrik - Wiyono, Giri (Sekolah Pascasarjana UGM, 2003)
This paper describes about a line outage which occurs on a 150 kV system in Ungaran area of Java - Bali interconnected electric power system. The effect of single line outage causes changes in the bus voltage system so that it is necessary to solve this problem by a contingency analysis. The aims of this research are to study a contingency analysis simulation program for solving the single-line outage problems and to plan optimally the Ungaran electric power system operation. In this way it will increase the reliability, security, and economy of the electric power system. This research is focused on the planning the Ungaran electric power system. The contingency analysis uses the Newton-Raphson power flow method. This methid has been successfully applied to a 59 buses, 78 lines network on a 150 kV Ungaran electric power system. The results show that 1) the contingency analysis using the Newton-Raphson power flow method is a reliable method for calculating changes in the bus voltage system while single-line outage occurs in a 150 kV Ungaran electric power system, 2) the single contingency caused by a transmission line outage results in changes at the generation bus and load buses voltages so that the buses exceed the out-of-limit voltages rated 142.5 kV until 157.5 kV, 3) the transmission line outage happening between Tambaklorok-2 bus and Sayung bus causes a bad off effect to stability of the Ungaran electric power system, and 4) the contingency analysis calculation results can be used to anticipate the operation planning optimally for detecting the transmission line outages in Ungaran electric power system. Thus the system planning can increases security and reliability of the Ungaran electric power system.